Accounting for Social Impact: Measuring Labor Welfare and Fair Compensation in SDG-Based Reporting - Nochh, Muhammad Yamin (Golden Ratio of Mapping Idea and Literature Format, 2025)
This study examines the role of social impact accounting in measuring labor welfare and fair compensation within Sustainable Development Goal (SDG)-based reporting frameworks. The primary objective of the research is to analyze how labor welfare indicators and compensation equity are conceptualized, measured, and integrated into sustainability reporting, with particular emphasis on their alignment with SDG 8 on decent work and inclusive economic growth. Employing a qualitative research design grounded in an extensive literature-based analysis, the study synthesizes peer-reviewed academic research, international institutional reports, and global sustainability reporting standards to identify dominant measurement practices, conceptual patterns, and methodological gaps in existing approaches. The findings reveal that labor welfare and fair compensation have increasingly been recognized as material social indicators in sustainability reporting; however, their measurement remains fragmented and inconsistent across organizations and regions. While current reporting frameworks provide general guidance on labor-related disclosures, they lack standardized metrics capable of capturing complex dimensions such as psychosocial well-being, living wage adequacy, wage equity, and the conditions of non-standard employment. The analysis further demonstrates that firms with more comprehensive labor welfare disclosures tend to exhibit stronger organizational legitimacy, enhanced stakeholder trust, and improved alignment with SDG objectives, yet many disclosures remain symbolic rather than substantive. The study concludes that integrating structured and empirically grounded labor welfare and compensation indicators is essential for strengthening the credibility and comparability of SDG-based reporting. The findings contribute to sustainability accounting literature by emphasizing the need for standardized social impact metrics and provide practical implications for organizations, policymakers, and investors seeking to advance decent work, wage fairness, and inclusive growth within global sustainability agendas.